Anterior vs non-anterior ST-segment elevation myocardial infarction: incidence of reinfarction and target vessel failure. (3rd May 2023) - Sa Couto, D; Alexandre, A; Faria, J; Luz, A; Campinas, A; Frias, A; Santos, R; Brochado, B; Silveira, J; Torres, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background and purpose: Left anterior descending (LAD) coronary artery occlusion has been associated with worse short-term outcomes and overall worse prognosis, there is still unclear data about the long-term risk of reinfarction in relation to the index culprit vessel. Methods: In this retrospective cohort study, between 2008 and 2013, a total of 584 patients were admitted with STEMI and were subject to emergent percutaneous coronary intervention (PCI). Of those, 535 (91.6%) were alive at hospital discharge, from which 532 were considered for the analysis, after excluding the missing cases. We stratified the individuals according to the culprit vessel in two groups: anterior myocardial infarction (MI) (LAD or left main stem (LM)), and non-anterior MI (circumflex (CX) or right coronary artery (RCA)). We followed the cases for a maximum of 8 years, censoring every event beyond. The primary endpoints were reinfarction and target vessel failure (TVF). Secondary endpoints included all-cause mortality, heart failure (HF) hospitalization and stroke. Mann-Whitney-U and Chi-square tests were used to compare baseline characteristics. Kaplan-Meyer survival analysis was used to obtain the survival curves. Univariate and multivariate analysis were done using Cox regression models. Results: Of the 532 individuals included in the analysis, 395 (74.2%) were men and the median age was 61 (+/- 19.8) years. The most common culprit vessel was RCA (45.5%), followed by LAD (41.2%), CX (13.2%), and lastly LM (0.20%). The median follow-up time was 6.94 (+/- 2.38) years. Overall, the anterior MI group presented at a higher Killip class (20.0% vs 14.8% in Killip class II-IV; p = 0.046) and had higher peak plasma level of high-sensitivity troponin T (6.16 vs 3.66 ng/ml; p < 0.001), suggesting larger infarct area. Left ventricle ejection fraction (LVEF) at discharge was also lower in the anterior MI group (reduced in 78, 3% vs 43.4%; p < 0.001). Multivessel disease was more common in the non-anterior MI group (49.5% vs 60.9%; p = 0.005), as was PCI of non-culprit vessels (15.5% vs 22.8%; p = 0.037) and the use of bare-metal stents (20.0 vs 51.6%; p < 0.001). There were no significant differences between the groups regarding the main comorbidities, except for peripheral artery disease, more common in the non-anterior MI group (4.10 vs 10.0%; p = 0.011). There was a higher risk of reinfarction in the non-anterior MI group which persisted after relevant variable adjustment (Adjusted hazard ratio 1.96; 95% CI [1.08 – 3.67]; p = 0.027) (Figure 1). There were no significant differences regarding the risk of TVF or any of the secondary outcomes. Conclusions: Although LAD/LM occlusion is thought to carry a worse short-term prognosis, non-anterior STEMI appears to be associated with a higher long-term risk of reinfarction. Despite higher rates of reinfarction, non-anterior STEMI patients have not been shown to have an excess mortality of HF hospitalizations in this cohort. Figure 1